SME Competitiveness Outlook 2019 - International Trade Centre (United Nations, 2019)
Increasing annual investments in small- and medium-sized enterprises (SMEs) in developing countries by 1 trilling would yield disproportionate dividends in terms of progress towards the Sustainable Development Goals (SDGs), while also delivering healthy returns for investors. Yet, less than 1% of the tens of trillions of dollars that global asset managers have under management is currently invested in developing country SMEs. This edition of SME Competitiveness Outlook explains how best to scale up private sector investment in developing country SMEs for sustainable development impact. It identifies four main streams through which investors, facilitators and enterprises can form partnerships for sustainable development, and it makes a strong case for investing in small businesses to achieve the Sustainable Development Goals.